English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

if x(x + y) = x^2 + xy shouldnt
2x(x + y) = 3x +xy? The answer is 2x^2 + 2xy.

Could someone please spell this out to me? =)

2006-12-20 05:38:09 · 5 answers · asked by grem 3 in Science & Mathematics Mathematics

5 answers

Everything inside the brackets is multiplied by the expression outside the brackets
2x(x+y) = (2x times x ) +( 2x times y)
= 2x*2 + 2xy

2006-12-20 06:02:29 · answer #1 · answered by simon c 2 · 1 0

When you multiply a polynominal by a monomial, you have to **multiply** the monomial by **each** item in the polynomial. So:

2(x + 4) = (2*x) + (2*4) = 2x + 8
3(x - 5) = (3*x) - (3*5) = 3x - 15
2(a + b + c) = 2a + 2b + 2c

Hope that helps.

2006-12-20 05:49:18 · answer #2 · answered by Navigator 7 · 1 0

It's hard to explain this without visuals. You are using the distributive property when doing this. You distribute the x (you monomial) to each term of the polynomial. (To think of it in silly terms, the bunny on the outside of the fence wants to jump over the fence and hop on each flower.) When you distribute the monomial, you multply the terms together. Hope this makes sense.

2006-12-20 05:46:27 · answer #3 · answered by bananie83 1 · 1 0

you are multiplying not adding, when doing multiplication of monomial times a polynomial you add the exponents of the factors if the bases are the same.and multiply rationals time rational.

2006-12-20 05:43:10 · answer #4 · answered by Ray 5 · 0 0

x(x+y)=x*x+x*y
x^2+xy distributive property
2x(x+y)=2x^2+2xy again the same rule
2x*x+2x*y
=2x^2+2xy

2006-12-20 05:41:22 · answer #5 · answered by raj 7 · 2 0

fedest.com, questions and answers